Bioactive sol‐gel glasses: Processing, properties, and applications. Issue 4 (14th February 2018) - Baino, Francesco; Fiume, Elisa; Miola, Marta; Verné, Enrica
Abstract: Sol‐gel route has shown its enormous potential in tissue engineering applications as an advantageous method for the production of bioactive glasses aimed at regenerating both hard and soft tissues. This review discusses the chemical aspects of the method with emphasis on the morphological, chemical, mechanical, and biological properties of sol‐gel derived materials. The attention will be particularly focused on sol‐gel bioactive glasses and sol‐gel foam scaffolds for bone regeneration. The advantages deriving from the versatility of the sol‐gel method compared to the traditional melt‐quenching route will be underlined in terms of bioactivity, compositions, and processing parameters.